Cross-examining the Role of the Directorate of Islamic Affairs, Nigerian Army in Eradicating Terrorism in the Northeast through the Counter-Narrative Programme - Uthman Okanlawon Sidiq; Abdul Gafar Olawale Fahm; Muhammad Bala Ahmad; Mustapha Adebayo Bello (Journal of Islamic History, 2026)
Globally, kinetic approaches (military force) have been the primary tool in combating terrorism. Since the rise of the Islamic State West Africa Province (ISWAP), Jamāʿat Ahl al-Sunnah li-l-Daʿawah wa al-Jihād “Association of the People of the Sunnah for Preaching and Jihād” popularly known as Boko-Haram in 2009, the Nigerian military has heavily invested in weaponry. Still, it continues to suffer significant casualties despite some successes. This has led to the adoption of a non-kinetic approach known as Counter-Narrative Programme under the control of the Directorate of Islamic Affairs (DOIA), which has been battling the activities of these terrorists’ group. This might be the reason why the non-kinetic approach, termed the counter-narrative approach, was introduced. What is the counter-narrative program? What military operations are taking place in the country? Which directorate of the Nigerian Army is saddled with the program? What is the role of the Directorate of Islamic Affairs (DOIA)? How efficient is the counter-narrative program? What led to the abandonment of the programme? And what is the way forward for the government to avert the subsequent explosion of new terrorist groups like the recent Lakurawa in order not to turn to another gorilla war? This paper is both qualitative and historical in approach, in interrogating the aforementioned issues. The paper concluded by dichotomizing the significance of the programme from an Islamic perspective, discussing the shortcomings of the programme, and ends with achievable recommendations. REFERENCES Abdul-Azim, A.Z. (2000), Ṣaḥiḥ Muslim Arabic-English, Riyadh: Darussalam Agbiboa, D E. (2013), “No Retreat, No Surrender: Understanding the Religious Terrorism of Boko Haram in Nigeria.” Ajala, O. (2018), “Formation of Insurgent Groups: MEND and Boko Haram in Nigeria.” Small Wars & Insurgencies 29, no. 1, 112–130.   Ajala O. (2025), "Countering Terrorism in Nigeria and the Lake Chad Basin: Reassessing the Role of Vigilantism as a Counterterrorism Initiative", in Taylor & Francis, https://www.tandfonline.com/doi/full/10.1080/19392206.2025.2458409, accessed 10-02-2026 Alex S. (2014). “Key Concept in Intercultural Dialogue, in the International Centre for Counter-Terrorism Bola G.A (2017), “Civilian Joint Task Force and Nigeria’s Counter-Terrorism”, in “Terrorism and Counter-Terrorism War in Nigeria: Essays in Honour of Lieutenant Tukur Yusuf Buratai” ed. Pius A. and Waziri A, Department of Army Standards and Evaluation, University of Lagos Press and Bookshop Ltd, Nigeria, 492-520 Canadian Forces Joint Publication Operation (2010), “Canadian Forces Joint Publication Operation. CFJP 3.0 Operation/Issued on authority of the Defence Staff, https://publications.gc.ca/site/eng/364825/publication.html  accessed 04-01-2025 Chinedu Asadu, (2020), “Army to launch ‘Operation Crocodile Smile’ in south-east”, in https://www.thecable.ng/army-to-launch-operation-crocodile-smile-in-south-east/ accessed 01-02-2026 David, J. O. (2013). “The root causes of terrorism: an appraisal of the socio-economic determinants of Boko Haram terrorism in Nigeria” (Doctoral dissertation); Amusan, Lere, and Samuel Oyewole. “Boko Haram terrorism in Nigeria: A reflection on the failure of democratic containment.” Politeia 33, no. 1 (2014): 35–49. Don John O.O. (2017), “Terrorism and Counter Terrorism Strategies in Nigeria: An Analytical Discourse” in “Terrorism and Counter-Terrorism War in Nigeria: Essays in Honour of Lieutenant Tukur Yusuf Buratai” ed. Pius A. and Waziri A, Department of Army Standards and Evaluation, University of Lagos Press and Bookshop Ltd, Nigeria, 511-536 Directorate of Islamic Affairs (2020) “Compilation of History of NA Formations Units and Establishments Nigerian Evans, O, and Ikechukwu K. (2019). “The Impact of Poverty, Unemployment, Inequality, Corruption and Poor Governance on Niger Delta Militancy, Boko Haram Terrorism and Fulani Herdsmen Attacks in Nigeria.” International Journal of Management, Economics and Social Sciences (IJMESS) 8, no. 2 (2019): 58–80. Katie P & Tim H, (2015), “Boko Haram overtakes ISIS as world’s deadliest terror group” in https://edition.cnn/2015/11/17/world/global-terror-report/index.html, accessed 04-01-2025 Marc-Ikemenjima D (2016), Money, sex or Revenge: Why are Nigerian Youths Joining the Boko Haram Terror Group? In The Nerve, 25 February, 2016, http://thenerveafrica.com/4064/money-sex-orrevenge-why-are-nigeria-youths-joining-thebokoharam-terror-group/ accessed 13-08-2016 Ministry of Defense (2025), Retrieved from https://defence.gov.ng/army-affairs/  04-01-2025 Muhammad B.A.D (2022),” Appraisal of the Nigerian Army Counter Narrative Programme: An Islamic Exposé”, An unpublished Dissertation, submitted to the Department of Religions and Peace Studies, Faculty of Arts, Lagos State University, Ojo. In partial Fulfilment for Award of Master of Arts (Islamic Studies) Mustapha S.G., Structured Interview (Brig-Gen SG Rtd) was the former Director of Islamic Affairs, Nigerian Army, 60, at Headquarters Islamic Affairs Bonny Camp, Lagos, October 11, 2023 Nigerian Army. (2014). The Nigerian Army Information Brief, Institute of Army Education Nigerian Army. (2020). Report on Counter-Narrative 2007-2020 Nigerian Army. (2020). “Nigerian Army in Joint Operations, Synergy and Holistic Approach to New Trends of Security Breaches”, NARC, Abuja Nigerian Army. (2021). Strategy in the North-East. Report Nigerian Army Education Corps. (2000). History of the Nigerian Army 1863-1992, Nigerian Army Resource Centre Okeke-Korieocha I, (2023), “Ngarannam: The Homecoming’, a story of displaced Nigerians from refugee camps back home”, https://businessday.ng/bd-weekender/article/ngarannam-the-homecoming-a-story-of-displaced-nigerians-from-refugee-camps-back-home/ accessed 04-01-2025   Olatunji O, (2024), Life returns to Borno night market sacked by insurgents, https://dailytrust.com/life-returns-to-borno-night-market-sacked-by-insurgents/, accessed 04-01-2025 Olubunmi A. (2017), “The Media and the War against Terrorism in Nigeria” in “Terrorism and Couter-Terrorism War in Nigeria: Essays in Honour of Lieutenant Tukur Yusuf Buratai” ed. Pius A. and Waziri A, Department of Army Standards and Evaluation, University of Lagos Press and Bookshop ltd, Nigeria, 567-584 Onuoha, F.C (2011) Nigeria’s Vulnerability to Terrorism: The Imperative of a Counter Religious Extremism and Terrorism (CONREST) Strategy. Peace and Conflict Monitor, University of Peace, http://www.monitor.upeace.org/innerpg.cfm?id_article=772, accessed 07-02-2026 Pius A. and Waziri A. (2017), “Terrorism and Counter-Terrorism War in Nigeria: An Overview” in “Terrorism and Counter-Terrorism War in Nigeria: Essays in Honour of Lieutenant Tukur Yusuf Buratai” ed. Pius A. and Waziri A, Department of Army Standards and Evaluation, University of Lagos Press and Bookshop Ltd, Nigeria, 1-16 Sidiq, U.O., (2019), “An Epistemological Appraisal of Boko-Haram’s Activities and Islamic Canon on Terrorism in Nigeria”, in Religious Violence and Conflict Management in Africa: Phenomenological and Epistemological Engagements, edited by Elias G. Konyana and Danoye Oguntola-Laguda, 487 Whitecliff, Harare, Zimbabwe: Africa Institute for Culture, Peace, Dialogue & Tolerance Studies, 57-79 Sidiq, U.O. (2019), “A Critical Review of 1999 Odi Massacre in Nigeria from the Qur’anic Perspectives of Genocide” in The Journal of Nigeria Association of Teachers of Arabic and Islamic Studies (NATAIS), Shebiotiomo Publication, vol. 22, 71-93 Sidiq U.O. (2022), “Religious Reproach towards Extreme Ideologies and Violent Crime in The Society” in Sri Lanka Journal of Arabic and Islamic Studies, vol. 5, Issue 1, 43 Sidiq U.O. (2023), “Islamo-Jurisprudential Discourse on Ghila (Murder by Deception): The 2001 Zaki-Biam Bloodbath in Nigeria” in LASU Journal of Humanities, Faculty of Arts, Lagos State University, vol. 16, no. 2, 51-67 Udama, R.A. (2013) “Understanding Nigeria terrorism, its implications to national peace, security, unity and sustainable development: A discuss.” IOSR Journal of Humanities and Social Science 8, no. 5, 100–115. Wahab G.A. & Ogbogbo. (2020). “Issues of Terrorism, Insurgency and Security in Nigeria” in NARC, Abuja Yusuf. B.T. (2020) “Commander’s Role in Joint Operations Environment: Paradigms for Success in Addressing Current Security Challenges